Myalgia and Hematuria in Association with Clonidine and Arginine Administration for Growth Hormone Stimulation Tests - Meghan Glibbery; Adam Fleming; Rahul Chanchlani; Olufemi Abiodun Ajani; Norma Marchetti; Alexa Marr; M. Constantine Samaan (Case Reports in Medicine)
Growth hormone deficiency (GHD) in children has significant impacts on growth and metabolism. Two-agent GH stimulation tests are commonly used to diagnose GHD, and these tests are generally considered safe. We report the case of a 5-year 5-month-old boy with a history of anaplastic ependymoma who underwent GH stimulation testing for growth deceleration using clonidine and arginine. He developed bilateral calf myalgia and gross hematuria within 24 hours of the tests. Myalgia and hematuria resolved spontaneously. Importantly, the literature review and database searches for hematuria identified 6 cases with clonidine and 20 cases with arginine. This case highlights an unusual combination of adverse reactions to clonidine and arginine in children undergoing GH stimulation testing to assess for GHD. Pediatric endocrinologists need to be aware of the potential for these side effects to allow appropriate management, and further studies are needed to clarify the mechanisms and frequency of these side effects. We recommend that patients and families need to be counselled about hematuria as an association of GH testing with these medications.